Land Conflicts and Social Insecurity in the Municipality of Kpele 1 in the Face of Sustainability Challenges in Togo (Architecture Image Studies, 2026)
In the commune of Kpélé 1 in south-western Togo, land is considered, according to social norms, to be a shared inheritance. The community therefore establishes rules to specify the use, sharing and transfer of this precious asset among all members. Belonging to the ancestors, the first occupants, the land is passed on in various forms to descendants, adopted foreigners or buyers. The availability of land and its exploitation according to customary rules have long been the basis for cohabitation and peaceful coexistence between several social groups. However, it has become the subject of controversy and conflict with the deterioration of social ties and family breakdown due to the monetisation of society and the decline of the collectivist spirit. This research aims to highlight the issues at stake, to understand the traditional and modern rationales that contextualise conflicts, and to identify endogenous and exogenous resolution mechanisms in the face of the challenges of lasting peace and social cohesion. The results show that several factors contribute to land conflicts, ranging from urban dynamics to historical and legal factors. In addition, conflicts are complex, and their resolution depends on the level of categorisation. It is therefore necessary to disseminate the legal framework based on the Land and State Property Code and to organise interviews and awareness-raising sessions with all stakeholders to promote social cohesion and peace, which are key to sustainable development.